Static Analysis 16th International Symposium, SAS 2009, Los Angeles, CA, USA, August 9-11, 2009. Proceedings - Palsberg, Jens.; Su, Zhendong. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 16th International Symposium on Static Analysis, SAS 2009, held in Los Angeles, CA, USA in August 2009 - co-located with LICS 2009, the 24th IEEE Symposium on Logic in Computer Science. The 21 revised full papers presented together with two invited lectures were carefully reviewed and selected from 52 submissions. The papers address all aspects of static analysis including abstract domains, abstract interpretation, abstract testing, compiler optimizations, control flow analysis, data flow analysis, model checking, program specialization, security analysis, theoretical analysis frameworks, type based analysis, and verification systems.